Comedy for animators - Lyons, Jonathan (Jonathan C.) (CRC Press, 2016)
While comedy writers are responsible for creating clever scripts, comedic animators have a much more complicated problem to solve: What makes a physical character funny? "Comedy for Animators" breaks down the answer by exploring the techniques of those who have used their bodies to make others laugh. Drawing from traditions such as commedia dell arte, pantomime, Vaudeville, the circus, and silent and modern film, animators will learn not only to create funny characters, but also how to execute gags, create a comic climate, and use environment as a character. Whether you re creating a comic villain or a bumbling sidekick, this is the one and only guide you need to get your audience laughingExplanation of comedic archetypes and devices will both inspire and inform your creative choicesExploration of various modes of storytelling allows you to give the right context for your story and charactersTips for creating worlds, scenarios, and casts for your characters to flourish inCompanion website includes example videos and further resources to expand your skillset--check it out at www.comedyforanimators.comJonathan Lyons delivers simple, fun, illustrated lessons that teach readers to apply the principles of history s greatest physical comedians to their animated characters. This isn t stand-up comedy it s the falling down and jumping around sort "